The Technical Experimentation in contemporary plastic arts (Al-Academy, 2016)
The current research that entitled (t Technical Experimentation incontemporary plastic arts) deals with study in used techniques and the material's functioning and its variations in artwork.It present the following questions :- 1-Does technical experimentation for mate an important phenomenon in contemporary art.2-Does technical experimentation construct an ability in creating new constructive and formative achievement in plastic art ?.The research includes three chapters . the first one deals with the problem of the research and its limits with the specification of terms . the second chapter present the technical Experimentation in contemporary plastic art with shapes display . the third chapter involves conclusions with discussions . the three chapters are followed by bibliography